KUALITAS PROGRAM PERSIAPAN GURU TUGAS DI PONDOK PESANTREN MAMBAUL ULUM BATA-BATA PANAAN PALENGAAN PAMEKASAN - Muchlis Solichin; Moh. Hafidz; Hilmi Qosim Mubah (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
The assignment teacher is a santri who has fulfilled some criteria who are ready to serve, are deployed and sent to various institutions. This is a program from the Mambaul Ulum Bata-Bata Pamekasan Islamic boarding school. This research uses a qualitative approach with descriptive types. The advantages of the task teacher preparation program are: a) The use of integrated curriculum, b) the applied curriculum has the support of boarding school caretakers, c) the term M2 appears in order to coordinate prospective task teachers, d) there is a regional or block program, e) background the education of educators is arranged according to the field, f) the results of quality improvement in the form of the application and development of an existing curriculum, g) the development and improvement of quality at the Mambaul Ulum boarding school in Bata-Bata is carried out continuously and continuously. The obstacles faced by Islamic boarding schools in implementing the teacher preparation program are: a) the lack of skill and creativity of the teacher or educator in presenting the program, b) the pesantren programs are running less optimally due to minimal student interest in learning, c) programs implemented and implemented are less varied due to minimal facilities and finances.